Galectin‐1 Is Implicated in the Protein Kinase C ε/Vimentin‐Controlled Trafficking of Integrin‐β1 in Glioblastoma Cells - Fortin, Shannon (Blackwell Publishing Ltd, 2008)
Cell motility and resistance to apoptosis characterize glioblastoma (GBM) growth and malignancy. In our current work we report that galectin‐1, a homodimeric adhesion molecule and carbohydrate‐binding protein with affinity for β‐galactosides, is linked with cell surface expression of integrin β1 and the process of integrin trafficking. Using immunofluorescence, depletion of galectin‐1 through both stable knockdown and transient‐targeted small interfering RNA (siRNA) treatment induces an intracellular accumulation of integrin‐β1 coincident with a diminution of integrin‐β1 at points of cellular adhesion at the cell membrane. Galectin‐1 depletion does not alter the gene expression level of integrin‐β1. Transient galectin‐1 depletion effectuates as well the perinuclear accumulation of protein kinase C epsilon (PKCε) and the intermediate filament vimentin, both of which have been shown to mediate integrin recycling in motile cells. Our results argue for the involvement of galectin‐1 in the PKCε/vimentin‐controlled trafficking of integrin‐β1. The understanding of molecular mediators such as galectin‐1 and the pathways through which they drive the cell invasion so descriptive of GBM is anticipated to reveal potential therapeutic targets that promote glioma malignancy.